Deep Ultraviolet BGaN Quantum Dot structures - Saad, Yasmeen; Habbeb AL-Khursan , Amin (University of Thi-Qar Journal of Science, 2021)
This research studies boron-containing quantum dot (QD) structures that emit the ultraviolet. Ternary and quaternary lattice-matched structure:, , , , , , and and their TE and TM gain spectra, spontaneous emission, spontaneous polarization, and piezoelectric polarization have been examined in these structures. They have high TE and TM spectra under reducing boron content in the QD or barrier layer. The total polarization decreases for the Al-containing systems, which is preferred. Binary systems emit at 199nm, while the quaternary can have a peak wavelength near 235nm. Elongating of the wavelength to 290nm is possible with with high gain at a few boron contents.